PENGGUNAAN SPEECH ACT DALAM INTERAKSI SOSIAL PELAKU UMKM DI BANGKALAN - Dewi Badriyatu Toyiba (Journal of Social, Culture, and Language, 2024)
Abstract This study aims to identify the types of speech acts and analyse their classification in the social interaction of MSME actors in Bangkalan, Madura, using the theory of Gourge Yule (1996). Using descriptive qualitative method, data were collected through direct observation and recording of conversations between sellers and buyers. The analysis shows that illocutionary act is the most frequently used type of speech act, with dominance in directive, representative, and expressive classifications .Directive is mostly used to direct or request actions from interlocutors, while representative conveys factual information, and expressive is used to express gratitude or appreciation. These findings illustrate that interaction in the context of Bangkalan MSMEs is not only pragmatic but also influenced by local cultural values. These results are expected to provide insights for MSME actors in developing effective communication patterns that respect local cultural values.Keywords:Speech act, UMKM, bangkalan.